A Proposal of Alternative Models to Replace the South Korean Space Object Response Models. (February 2019) - Kim, Syeun; Choi, Eun-Jung; Cho, Sungki; Hong, Jeong Yoo
Abstract: This article reviews South Korea's response model for space object impacts, re-entries, and collisions. These are countermeasure models that are prepared for natural or artificial space objects falling in South Korea or colliding in space, and they employ the Ministry of Science and ICT (MSIT) to perform 4 stages that include prevention, preparation, response, and restoration. However, the article suggests that this process is inefficient given that the MSIT specializes in research and development but is expected to perform disaster response tasks in the event of natural or manmade space object impacts and re-entries. The research presents 2 alternative models to the current ones: the first model specifies that the MSIT and the Ministry of the Interior and Safety (MOIS) work together, and the second model designates the MOIS as the only agency responsible for the disaster response. These alternative models would more effectively handle disaster management than would the current models.